2020
DOI: 10.1155/2020/6648406
|View full text |Cite
|
Sign up to set email alerts
|

Research Activity among Academic Medical Staff during the COVID-19 Pandemic in Marrakesh

Abstract: Introduction. The COVID-19 pandemic has profoundly impacted the medical academic institutions and their activities. Our aim was to describe the research activity (COVID-19-related or preexisting research) of the academic staff at the medical school in Marrakesh, Morocco. Methodology. An online survey among faculty members explored the COVID-19-related research activity as well as the impact of the pandemic on preexisting research, related challenges, and coping strategies. The form was distributed via e-mail. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 32 publications
(35 reference statements)
0
19
0
Order By: Relevance
“…Another impact of this pandemic on these institutions could be a disruption of the preexisting research activity. 21…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another impact of this pandemic on these institutions could be a disruption of the preexisting research activity. 21…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 36.4% of responders thought that the research activity had markedly decreased during the COVID-19 pandemic, and the reasons for this recession were thought by majority (39%) due to a shift of interest in research to COVID-19 rather than diabetes per se. On the other side, a study was conducted by Adarmouch et al 21 in which an online survey among faculty members explored the COVID-19-related research activity, as well as the impact of the pandemic on preexisting research, related challenges, and coping strategies; 58.2% of respondents reported conducting COVID-19-related research, while 40% reported that routine research activities were suspended as a result of the pandemic. Major challenges to research in this context were the clinical activity workload, limited access to patients, and research personnel shortage.…”
Section: Discussionmentioning
confidence: 99%
“…Across all articles reviewed, online questionnaires were the most commonly applied method of data collection. Online questionnaires were used (a) as a single datacollection method in eight studies (Adarmouch et al, 2020;Aubry et al, 2021;Camerlink et al, 2021;Guintivano et al, 2021;Kappel et al, 2021;Myers et al, 2020;Ramvilas et al, 2021;Stamp et al, 2021) and (b) in conjunction with other data sources in two studies that included email exchanges, mentor's notes, and papers co-authored by the mentor and doctoral researchers, as well as their perceptions of the effectiveness of the mentoring programme or website analytics and post-conference surveys (Raby and Madden, 2021). One of the papers involved data collection in the form of documents posted to an openaccess preprint repository for social sciences (Cui et al, 2022).…”
Section: Methods and Participants In The Studiesmentioning
confidence: 99%
“…All other studies involved collecting data from human participants. The number of participants per study varied from small (e.g., 11 participants in and medium (e.g., 55 participants in Adarmouch et al, 2020) to large (e.g., 4535 in Myers et al, 2020). The majority of the authors drew on data that were collected from researchers at different academic ranks but emphasising the experiences of ECRs (Aubry et al, 2021;Camerlink et al, 2021;Guintivano et al, 2021;Kappel et al, 2021;Stamp et al, 2021).…”
Section: Methods and Participants In The Studiesmentioning
confidence: 99%
See 1 more Smart Citation